Kompetensi Konselor Sebaya Bagi Remaja Berbasis Keagamaan - Hartatik, Hartatik; Subari, Subari; Munawwaroh, Fabroy Fauziyatul; Haroen, Hilman; Rahayu, Supriati Hardi (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2022)
In this article, it can be seen through a literature review that peer-to-peer relationships are often associated with adolescent life. Students as academics are mostly still in that range, especially at the undergraduate level. They are the ones who are vulnerable to national turmoil that triggers violent behavior. They require intense interaction with the same age group in responding to existing changes and developments.